Classification of Estrogen Receptor-Positive Breast Cancer Based on Immunogenomic Profiling and Validation at Single-Cell Resolution - Ma, Xianxiong; Chen, Hengyu; Yang, Ming; Ke, Zunxiang; Wang, Mengyi; Huang, Tao; Li, Lei (Frontiers in Cell and Developmental Biology, 2021)
Background: The aim of this paper was to identify an immunotherapy sensitive subtype for estrogen receptor positive breast cancer (ER+ BC) patients by exploring the relationship between cancer genetic programs and antitumor immunity via multi-dimensional genome-scale analyses. Methods: Multi-dimensional ER+ BC high-throughput data (raw count data) including gene expression profiles, copy number variations (CNVs) data, single nucleotide polymorphism (SNP) mutation data and relevant clinical information were downloaded from The Cancer Genome Atlas (TCGA) to explore immune subtype sensitive to immunotherapy using Consensus Cluster Plus algorithm based on multi-dimensional genome-scale analyses. One ArrayExpress dataset and 8 GEO datasets (GEO-meta dataset) as well as METABRIC dataset were used as validation sets to confirm the findings regarding the immune profiles, mutational features, and survival outcomes of the three identified immune subtypes. Moreover, development trajectory of ER+ BC patients from the single cell resolution level was also explored. Results: Using comprehensive bioinformatics analysis, three immune subtypes of ER+ BC (C1, C2, and C3; designated the immune suppressive, activation, and neutral subtypes, respectively) were identified. C2 was associated with upregulated immune cell signatures and immune checkpoint genes. Additionally, five tumor-related pathways (transforming growth factor [TGF]-β, epithelial–mesenchymal transition [EMT], extracellular matrix [ECM], interferon [IFN]-γ, and WNT signaling) tended to be more activated in C2 than in C1 and C3. Moreover, C2 was associated with a lower tumor mutation burden (TMB), a decreased neoantigen load, and fewer CNVs. Drug sensitivity analysis further showed that C2 may be more sensitive to immunosuppressive agents. Conclusions: C2 (the immune activation subtype) may be sensitive to immunotherapy, which provides new insights into effective treatment approaches for ER+ BC.